Seaweed kombucha : exploring innovation in marine resources and local perceptions - Jones, Martyn, 1986- (2021)
Verkefnið er lokað til 27.09.2022. Seaweed is a rapidly growing industry all over the world: several different species are harvested or cultivated for a plethora of industries, ranging from food and beverage, to cosmetics, medical, and biofuel industries. The productive marine waters around Iceland have resulted in a strong focus on fisheries, yet seaweed remains an underutilized resource. This study explores the perceptions of seaweed as a food and drink item in Iceland. The four-part thesis is designed as an innovation/feasibility exploration project using the case study of kombucha, a fermented tea which can be flavoured with various ingredients, as a novel seaweed product. First, heavy metal and iodine analysis were carried out on 2 different seaweed species and results were compared with EU regulations and Icelandic regulations. Second, different recipes of kombucha infused with seaweed were created, and a consumer taste test performed with a small focus group. Third, an online nation-wide survey was conducted to investigate overall perceptions of seaweed as a food item, comparing respondent demographics such as nationality, age, location (capital area vs rest of country) and general food habits. Fourth, a preliminary market exploration was also carried out using publicly available price data from grocery stores. Results show varying elevated levels of heavy metals and iodine in Saccharina latissima & Palmaria palmata. Furthermore, heavy metal guidelines for seaweed products are unclear in the Icelandic regulatory scheme. Taste-test results suggest that potential kombucha customers lie in the younger generations, whilst only 31% of Icelanders stated that they had heard of the drink, only 25% of Icelandic respondents had ever tried kombucha prior to the taste test. The nation-wide survey also confirmed that overall seaweed consumption in Iceland is quite low with around 1 in 10 respondents stating that they consume seaweed often, although there was a large number of respondents who are interested in ...